2006
DOI: 10.1158/1078-0432.ccr-05-2142
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Both CXC Chemokine Receptor 4 and Vascular Endothelial Growth Factor Proteins Predicts Early Distant Relapse in Stage II-III Colorectal Cancer Patients

Abstract: Purpose: CXC chemokine receptor 4 (CXCR4) and vascular endothelial growth factor (VEGF) are implicated in the metastatic process of malignant tumors. However, no data are currently available on the biological relationship between these molecules in colorectal cancer.We studied whether CXCR4 andVEGF expression could predict relapse and evaluated in vitro the contribution of CXCR4 in promoting clonogenic growth,VEGF secretion, and intercellular adhesion molecule-1 (ICAM-1) expression of colorectal cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 32 publications
9
141
2
1
Order By: Relevance
“…Many studies suggest that tumor cell migration and organspecific metastasis are critically regulated by chemokines and their receptors (21)(22)(23)(24)(25)(26)(27)(28)(29). The axis of CXCR4/CXCL12 plays an important role in metastasis of many tumors (9)(10)(11)(12)(13)(14)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that tumor cell migration and organspecific metastasis are critically regulated by chemokines and their receptors (21)(22)(23)(24)(25)(26)(27)(28)(29). The axis of CXCR4/CXCL12 plays an important role in metastasis of many tumors (9)(10)(11)(12)(13)(14)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 is a chemokine expressed by both cancer and stromal cells (21,22). Reportedly, CXCL12 and its receptor, CXCR4, play important roles in local progression, dissemination and immune evasion of colorectal cancer cells (23)(24)(25). Our recent study also suggested that stromal CXCL12 and CXCR4 expression following preoperative CRT is associated with distant recurrence and poor prognosis in RC (15).…”
Section: Univariate Analysismentioning
confidence: 83%
“…31,32 Another receptor that responds to CXCL12 is C-C chemokine receptor type 7 (CXCR7). 33 The induction of CXCR7 and CXCR4 activating pathways depends on cluster of differentiation 26 (CD26). 34 This enzyme suppresses CXCL12's ability to promote the metastasis and progression of the tumor.…”
Section: Impact On Cell Adhesion Moleculesmentioning
confidence: 99%